Evaporation‐Induced Vertical Alignment Enabling Directional Ion Transport in a 2D‐Nanosheet‐Based Battery Electrode. Issue 10 (30th January 2020) - Zhu, Yue; Ju, Zhengyu; Zhang, Xiao; Lutz, Diana M.; Housel, Lisa M.; Zhou, Yangen; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.; Yu, Guihua
Abstract: 2D nanosheets have been widely explored as electrode materials owing to their extraordinarily high electrochemical activity and fast solid‐state diffusion. However, the scalable electrode fabrication based on this type of material usually suffers from severe performance losses due to restricted ion‐transport kinetics in a large thickness. Here, a novel strategy based on evaporation‐induced assembly to enable directional ion transport via forming vertically aligned nanosheets is reported. The orientational ordering is achieved by a rapid evaporation of mixed solvents during the electrode fabrication process. Compared with conventional drop‐cast electrodes, which exhibit a random arrangement of the nanosheets and obvious decrease of rate performance with increasing thickness, the electrode based on the vertically aligned nanosheets is able to retain the original high rate capability even at high mass loadings and electrode thickness. Combined electrochemical and structural characterization reveals the electrode composed of orientation‐controlled nanosheets to possess lower charge‐transfer resistances, leading to more complete phase transformation in the active material. Abstract : Fabrication of electrodes based on dense and vertically aligned nanosheets is achieved via a controlled solvent‐evaporation process. The structurally advantageous architecture features excellent rate capabilities, lower charge‐transfer resistances, and more complete phase transformation of active material, much superior to the arrangement of stacked nanosheets commonly found using the conventional electrode preparation method.